A Hi-Tea talk on Islam...a backward religion [videorecording] - Saba Islamic Media ([Kuala Lumpur] : Saba Islamic Media, 2005)
A talk by Shah Kirit Kakukal Govindji, speaker on comparative religion and on Islam for non-muslims in the Hi-Tea organized by IIS Foundation. The spaker answered all the questions regarding Islam either from muslim or non-muslim
Title from container
Speaker: Shah Kirit Kakukal Govindji
Keywords: Islam; Islam -- Customs and practices